Neolithic crannogs: rethinking settlement, monumentality and deposition in the Outer Hebrides and beyond. (12th June 2019) - Garrow, Duncan; Sturt, Fraser
Abstract: Abstract : Artificial islets, or crannogs, are widespread across Scotland. Traditionally considered to date to no earlier than the Iron Age, recent research has now identified several Outer Hebridean Neolithic crannogs. Survey and excavation of these sites has demonstrated—for the first time—that crannogs were a widespread feature of the Neolithic and that they may have been special locations, as evidenced by the deposition of material culture into the surrounding water. These findings challenge current conceptualisations of Neolithic settlement, monumentality and depositional practice, while suggesting that other 'undated' crannogs across Scotland and Ireland could potentially have Neolithic origins.